MODEL MULTIVARIAT UNTUK MEMPREDIKSI ANGKA PUTUS SEKOLAH MAHASISWA DI PERGURUAN TINGGI DI WILAYAH PURWAKARTA - Herlan Priyatna Sukmarasa; Erpan Maulana; Muhammad Rizal Ardhiansyah; Osep Hijuzaman (Jurnal Manajemen Pendidikan, 2026)
Student dropout remains a persistent challenge in higher education, yet its underlying causes are often oversimplified as isolated academic or economic issues. This study examines student dropout potential using a multivariate perspective integrating academic, economic, social, and psychological factors, aiming to provide a contextual understanding of dropout behavior beyond single-factor explanations.A quantitative explanatory design was applied through a survey of active undergraduate students. Data were collected using structured questionnaires measuring academic conditions, economic background, social environment, psychological factors, and dropout status. Structural Equation Modeling (SEM) was employed to test direct and indirect relationships among variables, with measurement and structural models evaluated for validity, reliability, and hypothesis testing.The findings show that academic, economic, social, and psychological factors do not have statistically significant direct effects on student dropout status. Psychological factors also do not mediate the effects of external conditions on dropout decisions. These results indicate that dropout is shaped by complex and context-dependent dynamics rather than by single dominant variables within the studied context.